Development and characterisation of optogenetic tools for non-invasive control of cellular functions in epithelia - Ciampani, Victoria (2019)
Living organisms are constantly working to maintain homeostasis, a status of physiological balance, which is required for stable cellular functionalities. Internal and external factors act to disrupt homeostatic conditions, against which the organisms have to counteract in a continuous dynamic equilibrium. Epithelial cells, which demarcate the interface of the inside and the outside world and discriminate different compartments in animal organisms, are responsible for maintaining compartmental and bodily homeostasis. Epithelia constitute a diverse and heterogeneous tissue in the human body: their physiological functions are based on simple processes, such as the transport of ions and water through the layer to regulate fluid composition and preserve homeostasis. Impairments in such processes are often rooted in dysfunctions of the molecular structures behind these mechanisms, namely ion channels, transporters and pumps, and result in a variety of pathological conditions. Consequently, epithelia are rich targets for the development of drugs and therapies and there is growing interest in their study. The study of epithelial volume regulation and fluid transport has classically been invasive, drawing on electrophysiology and pharmacology to dissect and control ion transport for detailed characterisation of their physiology. The subject of this thesis is to create and optimise optogenetic tools to control and study vital properties of epithelial cells in future, such as their regulation of ion fluxes and volume flow. Optogenetics, a recently-born field of biotechnologies, mainly explored in neurophysiology to achieve precisely-timed generation of action potentials of selected populations of neurons, employs photon-gated channels and pumps to achieve control of ion flows across the membrane of genetically modified cells using light. The underlying thesis explored in this study is that the introduction and activation of these structures in epithelia, if sustained, could be capable of providing non-invasive control of epithelial membrane ion fluxes, homeostasis and cell volume, thus contributing to a complete vision of both pathophysiology and normophysiology of the tissue. In particular, the light-gated non selective cation channel Channelrhodopsin-2 from the green algae Chlamydomonas reinhardtii and the electrogenic chloride pump Halorhodopsin from the halophilic bacterium Natronomonas pharaonis will be harnessed in this thesis to create a novel toolkit for the manipulation of epithelial membrane fluxes relevant to the control of cell volume and fluid handling in a model for the human retinal pigment epithelium (RPE), whose dysfunctions have been associated to a variety of pathological conditions, eventually leading to blindness. The first half of this study focused on investigating the feasibility of introducing the optogenetic constructs Channelrhodopsin-2 (ChR2) and Halorhodopsin (eNpHR) into ARPE-19, an epithelial cell line derived from the human eye and routinely employed as an in vitro model of the RPE. Different approaches for the delivery of these opsin genes to the cells were evaluated and transfection was optimised both for ChR2 and eNpHR, following which the functionality of the channels, i.e. their ability to respond to light stimuli and drive the permeable ions through the membrane of the epithelial cells, was assessed. Activity of the optogenetic proteins was confirmed by the use of ion-sensitive fluorophores, in the case of ChR2 the calcium-sensitive Fura-2. Preliminary experiments performed using wild-type ChR2 (wtChR2), did not evidence major membrane ion permeability changes upon light exposure, as evaluated by calcium imaging. To overcome limitations of wtChR2, which is characterised by low channel conductance and rapid, slowly-reversible gating, my work moved to the selection and generation of point mutants of ChR2, designed to both modify overall membrane flux and longevity of the conducting state. Four single amino acid mutations were designed, generated and optimised in epithelially-targeted plasmids and promoters via site-directed mutagenesis, in order to screen for the most suitable mutants for controlling membrane ion dynamics in epithelial cells. Among the tested mutants, ChR2 variants L132C, H134R and T159C showed, through functional experiments, to be capable of providing optical control of the ARPE-19 cells, to the extent of controlling calcium dynamics. Moreover, implementation of a conventional microscope with specific optical filters and components resulted in the development of an integrated tool for the simultaneous photostimulation of the light-gated proteins and the recording of ion dynamics through the monitoring of ion-sensitive fluorescent indicators. Changes in ion permeabilities across the epithelial cell membrane and readout of cell output following light stimuli were achieved optically, removing the need for pharmacological agents or invasive microelectrodes. In conclusion, this work presents the design, creation and characterisation of a set of tools for a previously unreported application of light-gated optogenetic channels for the study of epithelial physiological processes, with the final goal of achieving non-invasive control of epithelial membrane ion fluxes and dynamics.